2015
DOI: 10.1007/s00394-015-1002-2
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid attenuates the effects of amyloid β oligomers on DNA methylation in neuronal cells

Abstract: These results suggest a mechanism by which folic acid may prevent Aβ oligomer-induced neuronal toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…,b; Liu et al . ). Together with these studies, the results of our study in humans suggest that correction of disturbed homocysteine metabolism early in adult life could reduce amyloid production and eventually prevent pathological amyloid accumulation in the brain.…”
Section: Discussionmentioning
confidence: 97%
“…,b; Liu et al . ). Together with these studies, the results of our study in humans suggest that correction of disturbed homocysteine metabolism early in adult life could reduce amyloid production and eventually prevent pathological amyloid accumulation in the brain.…”
Section: Discussionmentioning
confidence: 97%
“…Those results showed a beneficial effect from folic acid supplementation on cognitive functioning in later life [ 22 ]. It was also demonstrated that folic acid may modify Aβ accumulation in vivo [ 18 , 20 ] and in vitro [ 23 , 24 , 25 ]. In the present study, we investigated whether α-, β-, and γ-secretase are all involved the inhibition effect of folic acid on Aβ accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…One-carbon metabolism was also related to AD-like hallmarks (increased Aβ production) [ 21 , 38 ]. Previous studies have indicated that in neural cells or AD mice, folic acid supplement leads to higher availability of SAM and activities of DNA methyltransferases (DNMTs) [ 24 , 39 ], which are required for cellular methylation reactions. Therefore, altered miRNAs expression in present study may be related to the changing of methyl donor pool, along with increasing DNA methylation by folic acid administration.…”
Section: Discussionmentioning
confidence: 99%
“…These authors concluded that the capacity of oAβ to modulate gene expression could generate redox and methylation-dependent epigenetic effects that contributed to the pathology of AD [144]. This prospect has been supported by a recent study [145]. Using primary hippocampal neuronal cells and HT-22 cells, as well as AD transgenic mice, Liu et al [145] investigated the influence of oAβ on DNA methylation pathway in these cells, including DNMT activity, methylation potential of cells, APP and PS1 expression, cell viability, and the methylation of respective promoters.…”
Section: Admentioning
confidence: 75%
“…Using primary hippocampal neuronal cells and HT-22 cells, as well as AD transgenic mice, Liu et al [145] investigated the influence of oAβ on DNA methylation pathway in these cells, including DNMT activity, methylation potential of cells, APP and PS1 expression, cell viability, and the methylation of respective promoters. They found that oAβ caused neuronal toxicity with lowered DNMT activity, increased APP and PS1 expression, and decreased cell viability, each consequence of which could be prevented by folic acid via methylation-dependent pathways [145].…”
Section: Admentioning
confidence: 99%